Permeability and dust filtration behaviour of porous SiC ceramic candle filter. (2021) - Das, Dulal; Kayal, Nijhuma
Abstract: Porous SiC candle filter (∼660 mm L and 75 mm OD) were fabricated by ramming process using commercially available SiC powder (d50 = 212 μm), with and without alumina and small amount (3 wt%) of clay as the major binder phase additives, following heat treatment at 1400 °C in air. Depending on the composition, porosity of the candle filters varied from 36 to 39 vol% and C-ring strength varied from 15 to 23 MPa. The air permeability and dust filtration efficiency of the candle filter were evaluated using laboratory made test set up. At room temperature, Darcian (k1 ) and non-Darcian (k2 ) permeability parameters varied from 1.9 to 2.2 × 10 −12 m 2 and 5.4–9.72 × 10 −8 m, respectively. Airborne fly ash particle filtration tests showed good performance of SiC candle filter with filtration efficiency of >97%.